Effects of Intensive Therapy and Antecedent Hypoglycemia on Counterregulatory Responses to Hypoglycemia in Type 2 Diabetes - Davis, Stephen N. (American Diabetes Association, 2009)
OBJECTIVE—The physiology of counterregulatory responses during hypoglycemia in intensively treated type 2 diabetic subjects is largely unknown. Therefore, the specific aims of the study tested the hypothesis that 1) 6 months of intensive therapy to lower A1C <7.0% would blunt autonomic nervous system (ANS) responses to hypoglycemia, and 2) antecedent hypoglycemia will result in counterregulatory failure during subsequent hypoglycemia in patients with suboptimal and good glycemic control. RESEARCH DESIGN AND METHODS—Fifteen type 2 diabetic patients (8 men/7 women) underwent 6-month combination therapy of metformin, glipizide XL, and acarbose to lower A1C to 6.7% and 2-day repeated hypoglycemic clamp studies before and after intensive therapy. A control group of eight nondiabetic subjects participated in a single 2-day repeated hypoglycemic clamp study. RESULTS—Six-month therapy reduced A1C from 10.2 ± 0.5 to 6.7 ± 0.3%. Rates of hypoglycemia increased to 3.2 episodes per patient/month by study end. Hypoglycemia (3.3 ± 0.1 mmol/l) and insulinemia (1,722 ± 198 pmol/l) were similar during all clamp studies. Intensive therapy reduced (P < 0.05) ANS and metabolic counterregulatory responses during hypoglycemia. Antecedent hypoglycemia produced widespread blunting (P < 0.05) of neuroendocrine, ANS, and metabolic counterregulatory responses during subsequent hypoglycemia before and after intensive therapy in type 2 diabetic patients and in nondiabetic control subjects. CONCLUSIONS—Intensive oral combination therapy and antecedent hypoglycemia both blunt physiological defenses against subsequent hypoglycemia in type 2 diabetes. Prior hypoglycemia of only 3.3 ± 0.1 mmol/l can result in counterregulatory failure in type 2 diabetic patients with suboptimal control and can further impair physiological defenses against hypoglycemia in intensively treated type 2 diabetes.